A review of high-risk rapid weight loss behaviors with assessment of food intake and anthropometric measurements in combat sport athletes - Samadi, M.; Chaghazardi, M.; Bagheri, A.; Karimi, S.; Pasdar, Y. (Asian Journal of Sports Medicine, 2019)
Context: In most combat sports, athletes are classified according to their body weight, and many of them attempt to lose weight quickly.